Multi-channel marketing, branding and retail design : new challenges and opportunities - McIntyre, Charles, 1955-; Melewar, T. C.; Dennis, Charles (Emerald Group Publishing Limited, 2016)
Recently, many researchers have found that their work crosses the borders of design, branding and marketing. This orientation finds itself in contrast to the generally discipline-delineated world of academic journal publishing where cross-sector studies often find difficulties in acceptance (design-based work in marketing being particularly poorly represented). This unique book focuses upon service design, including retail and multi-channel marketing matters pertinent to the current age where physical contact with consumers has resurfaced as an enduring part of the marketing and branding landscape - complementary to online and virtual worlds. The span of the text goes from what may be regarded as micro-environmental issues of type design and the semiotics of brand meanings towards macro-environmental concerns of city design and ecological threat, all relative to living within any world (and all worlds) that businesses and consumers may co-create or are invited and welcomed to in their own multi-layered experience.